Merenda Cinta Melintas Budaya Hingga Senja Tiba (Studi Literatur tentang Perkawinan Antar-Budaya) - Anselmus Agung Pramudito (Faculty of Psychology Universitas Gadjah Mada, 2017)
Intercultural marriages have an actual percentage increase in different countries over time. One of the things that should be observed in intercultural marriage is that in married couples in the same culture, we will discover the uniqueness of individual personality traits that become one of the determinants for individuals in adapting to marital relationships, whereas in intercultural marriage relationships, there are many differences in cultural values brought by both individuals from birth and on the one hand it is possible to contradict so that it can complicate the process of adaptation in marriage and increase the likelihood of conflict during the marriage from time to time. From the literature review, the emergence of conflict due to cultural differences can lead to marital dissatisfaction that can lead to the intention and decision to divorce. In view of the growing intercultural marriage trends in many countries over time, this paper will specifically review the potential for conflict due to cultural differences in intercultural marriages, and will also address individual aspects of cultural differences as a triggering factor conflicts in intercultural marriages, and conflict management models that will be determinants of intercultural marriage achievement to provide a discourse on how to manage conflicts appropriately so that intercultural partners can sustain their marriage well into the elderly. In general, the use of integrating and compromising models in managing conflict will maintain a harmonious relationship that supports the achievement of marital satisfaction in intercultural couples (Cheng, 2010).